2010
DOI: 10.1007/s11340-010-9415-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature on Anisotropy Properties of an Aluminium Alloy

Abstract: International audienceThe temperature influence on the mechanical behaviour during plastic deformation of an AA5754-O aluminium alloy has been investigated by several experimental tests. First, monotonous tensile tests were carried out from room temperature up to 200°C with a classical tensile machine and with a less conventional testing apparatus involving the heating of the sample by Joule effect. With this second testing apparatus, the strain fields and tensile curves were obtained in function of temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 30 publications
1
27
0
1
Order By: Relevance
“…In another study [39], we have shown that a weak temperature dependence of the plastic anisotropy coefficients has been observed from room temperature up to 200…”
Section: Tensile Testsmentioning
confidence: 85%
“…In another study [39], we have shown that a weak temperature dependence of the plastic anisotropy coefficients has been observed from room temperature up to 200…”
Section: Tensile Testsmentioning
confidence: 85%
“…The core part of the novel biaxial testing system is the biaxial mechanism, which was designed to be used on a Gleeble 3800 [45]. The test apparatus was used to convert an input uniaxial force from a Gleeble into an output biaxial force of different loading ratios by coupling two rotatable plates to a central drive shaft, so that different strain paths were realised.…”
Section: Design Of a Biaxial Testing Apparatusmentioning
confidence: 99%
“…Cooling rate is a critical condition for hot stamping process and air jet cooling was connected to the quench system to control the cooling rate. Since only uniaxial tension/ compression can be obtained on a standard Gleeble [33], an ad-hoc test apparatus was used to transform uniaxial tension to biaxial tension under different loading ratios, so that different strain paths were realised. A high speed camera with the DIC system was used to capture the speckle pattern pre-painted on the surface of the concerned central area of the specimen and the stochastic pattern does not degrade at temperatures below 1093°C.…”
Section: The Principles Of the Experimental Designmentioning
confidence: 99%